Assessing the physical healthcare gap among patients with severe mental illness: large real-world investigation from Italy. Issue 5 (9th September 2021) - Corrao, Giovanni; Monzio Compagnoni, Matteo; Valsassina, Valeria; Lora, Antonio
Abstract : Background: One critical barrier to the uptake of mental health programmes is the so-called physical healthcare gap, a concern raised by the unattended physical comorbidity and early mortality of persons with severe mental illness. Aims: To evaluate the extension of physical healthcare gap among persons with severe mental illness under chronic drug therapies. Method: A population-based cohort study was carried out, using Lombardy healthcare utilisation databases. Prevalent patients treated with blood pressure-, lipid- or glucose-lowering agents were identified in January 2017. Among these, those who were receiving care for depression, schizophrenia, bipolar disorder or personality disorder formed the study cohort. A reference cohort was randomly selected from prevalent patients treated with chronic therapies without signs of severe mental disorders, to be matched with study cohort members for gender, age and number of previous contacts with the National Health System. One-year adherence to healthcare was measured through the proportion of days covered (drug adherence), and exposure to selected recommendations (clinical control adherence). Results: The 55 162 patients with severe mental illness were less likely to have high adherence to blood pressure-lowering, lipid-lowering or antidiabetic agents than the reference cohort by −24% (95% CI −26 to −22%), −10% (95% CI −14 to −6%) and −25% (95% CI −29 to −21%), respectively. The 9250 patients with diabetes and severe mental illness had −18% (95% CI −22% to −13%) reduced likelihood to meet recommendations for the clinical management of diabetes, compared with the reference cohort. Conclusions: Adherence to chronic drug therapies was sensibly worse among patients living with mental illness than those without signs of mental disorders.